Abusive supervision and hospitality employees' helping behaviors: The joint moderating effects of proactive personality and ability to manage resources. Issue 4 (8th April 2019) - Zhao, Hongdan; Guo, Limin
Abstract : Purpose: Drawing on the conservation of resources (COR) theory, this study aims to examine the influence of abusive supervision on hospitality employees' helping behaviors, especially, the joint moderating effects of proactive personality and ability to manage resources (i.e. RMA) in the hypothesized relationship. Design/methodology/approach: Using a two-phase design, this study gathered data from 353 employees of ten hotels located in China. To test the hypotheses, the study conducted a series of hierarchical multiple regression analyses. Findings: Findings demonstrated that abusive supervision was negatively related to hotel employees' helping behaviors. Moreover, both proactive personality and RMA jointly moderated the abusive supervision–helping behavior relationship. Specifically, when both proactive personality and RMA had high degrees, the abusive supervision–employees' helping behaviors linkage was weakest. Conversely, the strongest impact of abusive supervision on employees' helping behaviors occurred when both proactive personality and RMA were low. Practical implications: Hotel managers should reduce mistreatment and cultivate employees' both proactive personality and RMA, to inhibit the decline of helping behavior resulting from abusive supervision. Originality/value: First, the current study provides a novel theoretical underpinning of the COR theory to explain the abusive supervision–helping behavior association, particularly in the hospitality context. Second, this study contributes to the boundary effects of abusive supervision on helping behavior by investigating the moderating roles of individual differences (i.e. proactive personality and RMA).